Preferensi Konsumen Terhadap Atribut Produk Kebab Palestine Uncle Hasan - Doni Sahat Tua Manalu; Andini Firannisa; Akhdan Hadi Zahran; Fauziah Zumna Aqilah; Irlina Jilani; Rizky Iswanto (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
. The purpose of this study was to determine consumer preferences for kebab product attributes in Uncle Hasan's Palestine Kebab. The method used in the study is the Fishbein Analysis Method. This study uses 9 product attributes based on literature study references, namely taste, price, product content, size, packaging, service, product quality, product safety and product variations. Based on the results of the study, consumer preferences towards kebab attributes in Uncle Hasan's Palestine Kebab have no negative value. The preference value for the price attribute is 21.47 which is very positive, taste is 19.75 which is very positive, product content is 18.74 which is positive, size is 17.92 which is positive, packaging is 16.23 which is positive, service is 17.99 which is positive, product quality is 20.73 which is very positive, product safety is 20.60 which is very positive and product variation is 17.91 which is positive. The value of consumer preference for Uncle Hasan's Palestine Kebab kebab products as a whole is positive, with a value of 171.34.